DETERMINANTS OF DIVIDEND POLICY IN THE BANKING INDUSTRY LISTED ON THE INDONESIA STOCK EXCHANGE - Lintar Novianti Watanaya; Werner Ria Murhadi (LPPM UNIVERSITAS BINA INSAN, 2026)
Purpose: This study aims to analyze the determinants of dividend policy in the Indonesian banking sector, namely profitability (ROA), bank size (BSIZE), capital adequacy (CAR), and credit risk (NPL). Research Methodology: The data comprise 37 conventional commercial banks listed on the Indonesia Stock Exchange during 2020–2024 (185 observations). Two testing methods are applied simultaneously: panel data regression (Fixed Effect Model, via EViews 13) to examine the determinants of the Dividend Payout Ratio (DPR), and Multiple Discriminant Analysis (MDA, via SPSS) to determine the likelihood of dividend payment measured by the Propensity to Pay Dividends (PPD). Results: ROA, BSIZE, and CAR have a significant positive effect on DPR, whereas NPL has a negative but insignificant effect. The MDA indicates that BSIZE is the most dominant determinant of the decision to pay dividends, followed by ROA and CAR, with a classification accuracy of 82.2%. Conclusions: Bank dividend policy is multifactorial and unfolds as a two-stage decision: bank size and profitability chiefly drive the decision to pay dividends, while profitability and capital strength chiefly drive the size of the payout. Limitations: The relatively short observation period (2020–2024) was still influenced by post-pandemic credit-relaxation policies. Contributions: This study addresses the knowledge gap on dividend determinants in emerging-market banking by combining two complementary methods—regression to identify the determinants of dividend magnitude and MDA to classify the likelihood of dividend payment—offering benefits for dividend theory development, bank management, investors, and regulators